PENERAPAN GOOGLE MEET UNTUK PROSES MENDUKUNG KAMPUS MENGAJAR - Akhyar, Ahmad; Salsabila, Bela; Setiawan, Agung; Wahyudi, Sri (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
This research is motivated by the aim of preparing students to face social, and cultural changes, the world of work, and rapid technological advances so that human competence must be prepared to be better prepared to face the challenges of the times. Higher education institutions are required to be able to design and implement innovative learning processes so that students can achieve learning outcomes including aspects of attitude, knowledge, and skills optimally and always relevant. Independent campus is a program from the Ministry of Education. In an era of increasingly advanced information technology, the use of virtual platforms for learning activities has become increasingly important. This research aims to investigate the application of Google Meet as an effective tool to support the teaching process in the campus environment. The research method used is survey and qualitative data analysis. The survey was conducted on students and lecturers in various study programs at a university. The data collected includes user perceptions and experiences in using Google Meet for learning activities. The aim of the independent campus is that this policy aims to encourage students to master various sciences in preparation for future careers. The research results show that the use of Google Meet has made a positive contribution in supporting the teaching process on campus. Students recognize the advantages of this platform in facilitating communication and interaction between lecturers and students. In addition, lecturers also reported using Google Meet as an effective means for delivering lecture material, facilitating discussions, and providing feedback to students. However, this research also identified several challenges faced in implementing Google Meet. Factors such as limited internet access, technical constraints, and platform inflexibility can affect the user experience and effectiveness of using Google Meet as a learning tool